2022
DOI: 10.1021/acsami.1c19856
|View full text |Cite
|
Sign up to set email alerts
|

New Degree of Freedom in Determining Superior Piezoelectricity at the Lead-Free Morphotropic Phase Boundary: The Invisible Ferroelectric Crossover

Abstract: The morphotropic phase boundary (MPB) in leadfree ferroelectrics, starting from a quadruple point (QP), often displays large piezoelectric responses due to the flattened freeenergy profiles. In this work, we found that the QP composition rendering most flattened energy profiles could also exhibit abnormally low piezoelectric constants in Hf-doped BaTiO 3 . Such an anomaly in the strength of piezoelectricity can be ascribed to the progressive influence of additional strain heterogeneity induced by the substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Such phase coexistence naturally gives rise to the minimum energy barrier within the whole diagram; so, the MPB that derives from it yields a large response under small external fields. The minimum E C appearing at x = 0.3 suggested that the triple point of the system corresponded to the composition x = 0.3, similar to a previously reported (1−x)Ba(Ti 0.8 Hf 0.2 )O 3 -x(Ba 0.7 Ca 0.3 )TiO 3 system [28,29]. In addition, from x = 0.3 to 1.0, E C increased monotonously; this phenomenon was ascribed to the abovementioned greater potential well depths of PbTiO 3 [30].This could also explain the difference between the BZ 0.18 T-xBP 0.22 T system and the BZT-BCT system; for the BZT-BCT, the lowest E C was observed at the MPB composition BZT-0.5BCT [8].…”
Section: Ferroelectric and Piezoelectric Propertiessupporting
confidence: 87%
“…Such phase coexistence naturally gives rise to the minimum energy barrier within the whole diagram; so, the MPB that derives from it yields a large response under small external fields. The minimum E C appearing at x = 0.3 suggested that the triple point of the system corresponded to the composition x = 0.3, similar to a previously reported (1−x)Ba(Ti 0.8 Hf 0.2 )O 3 -x(Ba 0.7 Ca 0.3 )TiO 3 system [28,29]. In addition, from x = 0.3 to 1.0, E C increased monotonously; this phenomenon was ascribed to the abovementioned greater potential well depths of PbTiO 3 [30].This could also explain the difference between the BZ 0.18 T-xBP 0.22 T system and the BZT-BCT system; for the BZT-BCT, the lowest E C was observed at the MPB composition BZT-0.5BCT [8].…”
Section: Ferroelectric and Piezoelectric Propertiessupporting
confidence: 87%
“…Thus, a dense ferroelectric sample with optimum grain size is essential to attain higher value of piezoelectric coefficients. 79,91 The piezoelectric constant, a key parameter characterizing the piezoelectric properties of materials, provides a measure of their ability to convert mechanical stress into electrical voltage and vice versa. In this context, the piezoelectric constants were measured for all of the ferroelectric materials (1 − x)BZT5− (x)BCT8 with varying composition.…”
Section: Piezoelectric Propertiesmentioning
confidence: 99%
“…The quest for lead-free piezoelectric materials with a large electromechanical (EM) response is very important for nano electromechanical systems (NEMS) devices such as actuators, ultrasonic transducers, sensors, energy harvesters, nanopositioners, and micro-robotics [1][2][3][4] . A common strategy to increase piezoelectric response from non-centrosymmetric materials is to flatten the thermodynamic energy profile easing polarization rotation [5][6][7][8] . Such an energy landscape is seen at the morphotropic phase boundary (MPB) in materials such as Pb(Zr,Ti)O3 (PZT) and relaxor ferroelectrics, and in materials with many coexisting local orders (K0.5Na0.5NbO3-xBaTiO3 (KNN-BT, for e.g.)…”
Section: Introductionmentioning
confidence: 99%
“…Such an energy landscape is seen at the morphotropic phase boundary (MPB) in materials such as Pb(Zr,Ti)O3 (PZT) and relaxor ferroelectrics, and in materials with many coexisting local orders (K0.5Na0.5NbO3-xBaTiO3 (KNN-BT, for e.g.) [5][6][7][8][9][10] . In classic ferroelectrics, domain wall motion is a major contributor to the EM response, especially at lower frequencies 11,12 .…”
Section: Introductionmentioning
confidence: 99%